Composites from recycled polypropylene and rubberwood flour: Effects of composition on mechanical properties - Homkhiew, Chatree (Journal of Thermoplastic Composite Materials, 2013)
The mechanical properties of composites from recycled waste plastic and waste sawdust are of interest in trying to convert these waste streams to useful products. The development of these composites from natural fiber is therefore receiving widespread attention due to the growing environmental awareness. The effects of compositions were investigated including different grades of plastic (virgin and recycled) and amounts of wood flour, coupling agent, and ultraviolet (UV) stabilizer on mechanical and physical properties of polypropylene/rubberwood flour (RWF)composites. Virgin polypropylene gave better mechanical properties than recycled (recycled polypropylene (rPP)), both in composites and as unfilled plastic. RWF content exceeding 25 wt% enhanced the strength of RWF-reinforced rPP composites. The modulus and hardness of composites increased linearly with wood flour loadings. Maleic anhydride-grafted polypropylene (MAPP) as a coupling agent increased the strength, modulus, and hardness of the composites. However, addition of 1 wt% UV stabilizer degraded the mechanical properties. Therefore, 4 wt% MAPP content is recommended to achieve good mechanical properties of rPP/RWF composites, while the amount of UV stabilizer should be as small as possible to avoid its negative influence.